A qualitative study of occupational well-being for people with severe mental illness. (4th July 2017) - Milbourn, Benjamin; McNamara, Beverley; Buchanan, Angus
Abstract: Background/aim: People with severe mental illness (SMI) do not receive adequate attention in research or clinical practice. They are considered hard to reach and difficult to engage. Information is needed to help provide support for this vulnerable population. This paper aims to investigate the well-being of adults diagnosed with SMI and receiving Assertive Community Treatment (ACT) by applying the occupational well-being framework to the everyday activities of this vulnerable group of people. Materials and methods: Eleven adults diagnosed with an SMI, living in the community, participated in semi-structured interviews over a 12-month period. A longitudinal design was used to collect data through using field notes and audio recordings. For this paper, secondary analysis was conducted by coding the data deductively thereby investigating the participants' experiences in relation to the seven Occupational Well-being framework descriptors (accomplishment, affirmation, agency, coherence, companionship, pleasure and renewal). Results : Participants' everyday activities and occupational well-being appeared severely restricted and largely determined by the type of care they received. There was minimal evidence of the well-being descriptors, though all the participants reported experiencing some form of pleasure, even though some of the pleasurable experiences negatively impacted their health. Conclusion/significance: The episodic nature of SMI means that people living with an SMI require continuity in key relationships and support to achieve Occupational Well-being. Occupational therapists working with mental health consumers need to facilitate the types of activities that foster well-being through accomplishment, affirmation, agency and companionship, and that derive pleasure in healthy and positive ways.